Application of high intensity focused ultrasound combined with nanomaterials in anti-tumor therapy - Xuehui Zhang; Ningning He; Liang Zhang; Tong Dai; Zihan Sun; Yuqing Shi; Shangyong Li; Ning Yu (Taylor & Francis Group, 2024)
AbstractHigh intensity focused ultrasound (HIFU) has demonstrated its safety, efficacy and noninvasiveness in the ablation of solid tumor. However, its further application is limited by its inherent deficiencies, such as postoperative recurrence caused by incomplete ablation and excessive intensity affecting surrounding healthy tissues. Recent research has indicated that the integration of nanomaterials with HIFU exhibits a promising synergistic effect in tumor ablation. The concurrent utilization of nanomaterials with HIFU can help overcome the limitations of HIFU by improving targeting and ablation efficiency, expanding operation area, increasing operation accuracy, enhancing stability and bio-safety during the process. It also provides a platform for multi-therapy and multi-mode imaging guidance. The present review comprehensively expounds upon the synergistic mechanism between nanomaterials and HIFU, summarizes the research progress of nanomaterials as cavitation nuclei and drug carriers in combination with HIFU for tumor ablation. Furthermore, this review highlights the potential for further exploration in the development of novel nanomaterials that enhance the synergistic effect with HIFU on tumor ablation.